Pollen limitation and fruiting failure related to canopy closure in Calypso bulbosa (Orchidaceae), a northern food‐deceptive orchid with a single flower. (21st February 2013) - Abeli, Thomas; Jäkäläniemi, Anne; Wannas, Lauri; Mutikainen, Pia; Tuomi, Juha
<x xml:space="preserve">Abstract</x> Natural fruit set is constrained by pollen limitation and fruiting failure, and pollen limitation is expected to be especially severe in deceptive orchids. We performed hand cross‐pollinations in ten populations of a food‐deceptive orchid, Calypso bulbosa, under sparse and dense canopies in three non‐consecutive years. We explored the relationships between natural fruit set, pollen limitation and fruiting failure. Mean natural fruit set over the years was 60%, which is exceptionally high for a deceptive orchid. On average, hand cross‐pollination increased fruit set by 23%. Among open‐pollinated plants that did not set a fruit, 55.5% were estimated to be pollen limited and 44.5% to be limited by fruiting failure, i.e. inability to set a fruit after pollination. In species with high natural fruit set, hand cross‐pollination experiments may not always detect statistically significant pollen limitation. In our case, pollen limitation tended to become significant when the natural fruit set dropped below 60%. Canopy cover had a significant effect on fruiting failure, which was more severe under a dense canopy. Although our results demonstrate pollen limitation in many cases, they also highlight the fact that food deception can be a very effective pollination strategy. © 2013 The Linnean Society of London, <mixed-citation id="boj12014-cit-0041" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"><source content-type="journalTitle">Botanical Journal of the Linnean Society</source>, <year>2013</year>, <volume>171</volume>, <fpage>744</fpage>–<lpage>750</lpage>.</mixed-citation>